Comparison of selected inhibitor doped sol–gel coating systems for protection of mild steel. (May 2014) - Suleiman, R.; Khaled, M.; Wang, H.; Smith, T. J.; Gittens, J.; Akid, R.; Mohamad El Ali, B.; Khalil, A.
<x content-type="archive" xml:space="preserve">Abstract</x> Current legislation around the use of antifouling and anticorrosion coatings has increased the need to find an environment friendly alternative to existing biocide containing pretreatments for steel structures exposed to sea water. Sol–gel technology offers a solution to fouling and corrosion inhibition since sol–gel chemistry lends itself ideally to functionalisation with a variety of components, for example, corrosion inhibitors. In this study, we have utilised the above mentioned approach in order to produce an inhibitor doped sol–gel protective coating on mild steel. The corrosion protection performance of three inhibitors, i.e. SD (Shieldex303), MOLY (Moly-White101ED-PLUS) and ZAPP (Heucophos ZAPP), added individually to a sol–gel, and applied to mild steel Q panels, were evaluated using electrochemical impedance spectroscopy. The inhibitor containing coatings were shown to protect against corrosion of mild steel; the coatings containing the inhibitors Moly and ZAPP were the most effective of the systems tested. Highlights Sol–gel coatings are potential candidate systems for the protection of mild steel substrates. Sol–gel chemistry allows a variety of corrosion inhibitors to be incorporated into the sol–gel coating matrix. Evaluation of corrosion inhibition efficiency of sol–gel coatings can be assessed using electrochemical impedance spectroscopy (EIS).